Taxogenomic Analyses of Starmerella Gilliamiae F.A, Sp. Nov. and Starmerella Monicapupoae F.A., Sp. Nov., Two Novel Species Isolated from Plant Substrates and Insects - Cubillos-Riffo, F; Araya, M (Microbiology Society, 2024)
Four yeast isolates collected from flowers from different ecosystems in Brazil, one from fruit of Nothofagus alpina in Argentina, three from flowers of Neltuma chilensis in Chile and one obtained from the proventriculus of a female bumblebee in Canada were demonstred, by analysis of the sequences of the internal transcribed spacer (ITS) region and D1/D2 domains of the large subunit rRNA gene, to represent two novel species of the genus Starmerella. These species are described here as Starmerella gilliamiae f.a, sp. nov. (CBS 16166T; Mycobank MB 851206) and Starmerella monicapupoae f.a., sp. nov. (PYCC 8997T; Mycobank MB 851207). The results of a phylogenomic analysis using 1037 single-copy orthogroups indicated that S. gilliamiae is a member of a subclade that contains Starmerella opuntiae, Starmerella aceti and Starmerella apicola. The results also indicated that S. monicapupoae is phylogenetically related to Starmerella riodocensis. The two isolates of S. monicapupoae were obtained from flowers in Brazil and were probably vectored by insects that visit these substrates. Starmerella gilliamiae has a wide geographi-cal distribution having been isolated in flowers from Brazil and Chile, fruit from Argentina and a bumblebee from Canada. © 2024 The Authors.